2008
DOI: 10.1017/s0272263108080741
|View full text |Cite
|
Sign up to set email alerts
|

THE CLAUSE-INITIAL POSITION IN L2 GERMAN DECLARATIVES : Transfer of Information Structure

Abstract: This article investigates the information structure of verb-second (V2) declaratives in Swedish, German, and nonnative German. Even though almost any type of element can occur in the so-called prefield, the clause-initial preverbal position of V2 declaratives, we have found language-specific patterns in native-speaker corpora: The frequencies of prefield constituent types differ substantially between German and Swedish, and Swedish postpones new (rhematic) information and instead fills the prefield with given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 21 publications
5
51
2
4
Order By: Relevance
“…The learners in this study do better than Bohnacker & Rosén's (2008) learners of the reverse language combination. This is likely to be an effect of increased exposure (input) during their three and six or more years in a dominant L2 environment vis-à-vis foreign language classroom learning for a maximum of six years in Bohnacker & Rosén's study.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The learners in this study do better than Bohnacker & Rosén's (2008) learners of the reverse language combination. This is likely to be an effect of increased exposure (input) during their three and six or more years in a dominant L2 environment vis-à-vis foreign language classroom learning for a maximum of six years in Bohnacker & Rosén's study.…”
mentioning
confidence: 60%
“…
In a recent study of the clause-initial position in verb-second declaratives (the prefield), Bohnacker & Rosén (2008) found significant differences between native Swedish and German concerning the frequencies with which constituents occurred in the prefield, as well as qualitative differences concerning the mapping of information structure and linear word order: Swedish exhibited a stronger tendency than German to place new information, the so-called rheme, later in the clause. Swedish-speaking learners of German transferred these patterns from their L1 to German.
…”
mentioning
confidence: 99%
“…For example, Cai (1998) investigated the topic-prominent errors in English essays written by Chinese university students in a quantitative approach and found that more than 20% of the errors were results of L1 transfer. Bohnacker and Rosén (2008) found language-specific patterns in native-speaker corpora: the frequencies of prefield constituent types differed substantially between German and Swedish, and Swedish postponed new (Rhematic) information and instead filled the prefield with given (Thematic) elements and elements of no or low informational value (e.g., expletives) to a far greater extent than German in a study investigating information structure of verb-second declaratives in Swedish, German, and nonnative German. These learners over-applied the Swedish principle of Rheme later in their second language German, indicating first language (L1) transfer at the interface of syntax and information structure, especially for structures that were frequent in the L1.…”
Section: The Factors That Influence English Learners' Themes and Themmentioning
confidence: 92%
“…von Stutterheim, 2003;Lambert et al, 2008, for spatial and temporal information; Bohnacker & Rosén, 2008, for the impact of information structure on word order; Ahrenholz, 2005;Leclercq & Lenart, 2013, for referring expressions). The picture emerging r om studies addressing the L2 acquisition of additive and contrastive linking of information units in discourse Benazzo et al, 2012;Tomita, 2013) is rather mixed.…”
mentioning
confidence: 99%